2007
DOI: 10.1038/sj.bjc.6604010
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin induces apoptosis via a MRP1-dependent mechanism in doxorubicin-resistant small-cell lung cancer cells overexpressing MRP1

Abstract: Small-cell lung cancers (SCLCs) initially respond to chemotherapy, but are often resistant at recurrence. The non-steroidal anti-inflammatory drug indomethacin is an inhibitor of multidrug resistance protein 1 (MRP1) function. The doxorubicin-resistant MRP1-overexpressing human SCLC cell line GLC 4 -Adr was highly sensitive for indomethacin compared with the parental doxorubicin-sensitive line GLC 4 . The purpose of this study was to analyse the relationship between hypersensitivity to indomethacin and MRP1 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…[37][38][39] Different mechanisms have been proposed for the induction of indomethacin-mediated apoptosis, including the inhibition of multidrug-resistance protein 1 function [40] and the suppression of the STATs/Bcl-xL signaling pathway. [41] It is becoming increasingly clear that cytotoxic agents and anti-inflammatory drugs may simultaneously inhibit multiple targets.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Different mechanisms have been proposed for the induction of indomethacin-mediated apoptosis, including the inhibition of multidrug-resistance protein 1 function [40] and the suppression of the STATs/Bcl-xL signaling pathway. [41] It is becoming increasingly clear that cytotoxic agents and anti-inflammatory drugs may simultaneously inhibit multiple targets.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, antiapoptotic roles were also suggested for other ABC-transporters including BCRP [123] . On the other hand, it has been reported that the non-steroidal anti-inflammatory drug indomethacin, an inhibitor of MRP1, induces apoptosis in MRP1-expressing lung cancer cells through an MRP1-dependent mechanism [124] . Thus, possible pro-apoptotic features of ABCtransporters should also be considered.…”
Section: Modulation Of Cellular Death Pathwaysmentioning
confidence: 99%
“…[15] Numerous studies have suggested that aspirin and/or other NSAIDs can be effective in the prevention and/or treatment of malignancies, such as cancers of the colon, [16] breast, [17,18] lung, [19] pancreas, [20] prostate, [21,22] ovarium, [23] squamous cell carcinoma and melanoma, [24] etc. Different NSAIDs have been reported to inhibit the growth and survival of cell lines established from a wide variety of cancers, including gastric cancer, [25,26] cancers of the colon, [27] lung, [28] urinary bladder, [29] osteosarcoma, [30] etc.…”
Section: Introductionmentioning
confidence: 99%